Touring the screen : tourism and New Zealand film geographies - Leotta, Alfio (Intellect, The University of Chicago Press, 2011)
"Following the success of prominent feature films shot on location, including Tolkien’s wildly popular The Lord of the Rings, New Zealand boasts an impressive film tourism industry. This book examines the relationship between New Zealand’s cinematic representation—as both a vast expanse of natural beauty and a magical world of fantasy on screen—and its tourism imagery, including the ways in which savvy local tourism boards have in recent decades used the country’s film representations to sell New Zealand as a premiere travel destination. Focusing on the films that have had a strong impact on marketing strategies by local tourist boards, Touring the Screen will be of interest to all those working and studying in the fields of cinema, postcolonial history, and tourism studies." --